THE DEGREE OF FAT UNSATURATION IN THE TISSUE AND POTENTIAL IMMUNE RESPONSE OF BROILER FED CHLORELLA SP. - Sugiharto, Sugiharto; Henckel, P; Lauridsen, C (ANIMAL PRODUCTION, 2010)
This study was carried out to investigate the effect of Chlorella sp. administered in the diet of broilers on the degree of fat unsaturation, ratio of EPA to AA in the tissue and potential immune response of broiler. A total of 90 heads of one-day-old Ross chicks were assigned in completely randomized design by 3 dietary treatments with 6 repetitions and 5 chicks in each pen. The diets were T1: control (basal diet without enrichment with Chlorella sp.); T2: basal diet enriched with 5-g of Chlorella sp./kg feed; T3: basal diet enriched with 10-g of Chlorella sp./kg feed.  Skinless breast meat was sampled for FA determination at d-36. Chickens were vaccinated at d-6 and d-17 with live vaccine against ND to activate antibodies production, and then 2 ml of blood was collected at d-24 for IgG and IgM quantification. Administration of Chlorella sp. in broiler?s diet had no significant effect on the degree of fat unsaturation, the ratio between EPA and AA contained in the breast muscle and the concentration of IgG and IgM of broiler. In conclusion administration of Chlorella sp. from tropical marine origin in the diet of broiler has no significant effect on the degree of fat unsaturation, ratio of EPA to AA in the tissue, and potential immune response of broiler. The culture temperature in which the Chlorella sp. was cultivated may affect the FA composition of Chlorella sp. (Animal Production 12(2): 96-99 (2010)Abbreviations: AA: arachidonic acid, ALA: ?-linolenic acid, EPA: eicosapentaenoic acid, FA: fatty acids, LA: linoleic acid, PGE2: Prostaglandin E2, PUFA: polyunsaturated fatty acids, SFA: saturated fatty acidKey Words: antibody, broiler, Chlorella sp., fatty acid, PUFA